pH-Dependent Molecular Behaviors of a New Potential Color Additive: 4[6-(1-carboxyethyl)-2-hydroxy -1-naphthyl]diazenyl-3,5- dinitro Benzoic Acid - Idowu, Sunday Olakunle (Journal of Applied Solution Chemistry and Modeling, 2012)
Phenyl azo hydroxynaphthalene (PAHNP) is the pharmacophore in certain color additives (e.g. sunset yellow, FD & C yellow No. 6) approved for use in human foods, drugs and cosmetics. The azo compound, 4[6-(1-carboxyethyl)-2-hydroxy -1-naphthyl] diazenyl-3,5-dinitrobenzoic acid (AZ-03) is a new, non-genotoxic, PAHNP analog, in a mono-azo chemical library. Process understanding of pH dependent behaviors of the highly functionalized molecule, is a critical aid to its identification. Absorption spectra of a fixed concentration of AZ-03 [3.30 x 10-5 M] in buffer solutions of varied pH were recorded. Spectra overlay suggested isosbestic point exists around 520 nm. Absorbance measurements of solutions (1.10 x 10-5 M) of pH 7, 10 and 11 were taken at 522, 524, 526 and 528 nm. Relative contribuiton of variables to overall variance was; wavelength (7%, p = 0.16), pH of media (57%, p < 0.0001), interaction between pH and wavelength (7%, p = 0.46, 2-way ANOVA, Bonferroni test). The probability that signal difference across pH was due to chance was 4 times greater at 522 nm (p=0.29) relative to 524 nm (p=0.08, 1-way ANOVA). The orange, unionized specie and violet, ionized specie both exhibited intense absorption, with molar absorptivities of 14,600 (490 nm) and 12,800 (550 nm) [L mol-1 cm-1 ] respectively. AZ-03 was degraded by pseudo first-order kinetics in alkaline medium by specific-base catalysis. It was shown with some statistical rigor that the dye exhibits isosbestic point at 522 nm . Base-catalyzed degradation gave a non-linear and diagnostic rate-pH profile. These findings could aid precise authentication of this potential color additive, and thus facilitate further understanding and studies of its solution chemistry.